The Study of Automatic Pattern Generation for MTM Product on Gerber’s Accumark Software - Nguyen, Phuong Linh; Duong, Thi Hoan (JST: Engineering And Technology For Sustainable Development, 2022)
This study aims to analyze the automatic pattern design process using the CAD Accumark Gerber system. The basic pattern was made by the Wizard tool of Accumark after that creating the MTM pattern. The Made-to-measure (MTM) pattern is cut and sewn using a standard-sized base pattern, then constructed to fit each customer individually. According to the research, the basic MTM patterns were changed the important points of body measurements for pattern design by grading rules and alteration rules based on the research of Vietnam Textile research Institute JSC No 089.10 RD/HĐ-KHCN. The basic pattern has been designed from size tables of women’s clothing, then adjusted the sample measurements to create the MTM pattern. The result of the study was women’s pant basic sample pattern; Guide of Grading rule pattern size, Alteration point numbering, Alteration Rule, Size code of the women’s pants to design and adjustment on the Gerber CAD system can use for the making MTM Pattern for the apparel manufacturing process.